Potential for Organ procurement potential in an emergency hospital of Sergipe - Nogueira, Emília Cervino; Pereira, Carlos Umberto (Brazilian Journal of Transplantation, 2007)
Purposes: To estimate the potential for organ donors in an emergency reference hospital; to describe its profile; to analyze the causes for the non-donation. Methods: Quantitative, descriptive, and retrospective study using data collected from medical records of up to 65 years old patients dead due to traumatic brain injury, cerebrovascular stroke, and primary brain tumor along the years 2005 to 2007. Results: From 645 medical records assessed, 219 presented record suggestive for brain death, and 126 had Declaration Term of Brain Death duly filled out. The median age of these potential donors was 29.5 years, prevailing male donors (77%), victims of traumatic brain injury (68%), and at Emergency Unit (41%). Half of them presented signs of brain death in the first two hospitalization days, and only 7% became effective donors, being the family refusal (31%) and irreversible cardiac arrest (28.6%) the main cause for the non-donation. Time between the first record and the removal of organs was longer than 30 hours in 75% of donors. Conclusions: Results of the study showed a low notification and diagnosis of brain death rates resulting in a reduced amount of potential donors, and consequently, a small amount of died donors’ organs and tissues. Rates of family refusal and irreversible cardiac arrest suggest the need of educational actions driven to the health professionals and the society in general.